"Being with" while retaining and asserting professional midwifery power and authority in home birth. Issue 2 (2014) - Colm O'Boyle
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to describe what it is like to be a midwife in the professionally isolated and marginalised arena of home birth in Ireland and to explore whether the organisation of home birth services and professional discourse might be undermining the autonomy of home birth midwives. Design/methodology/approach – This paper is drawn from auto‐ethnographic field work, with 18 of the 21 self‐employed community midwives (SECMs) offering home birth support to women in Ireland from 2006 to 2009. The data presented are derived from field notes of participant observations and from interviews digitally recorded in the field. Findings – Home birth midwives must navigate isolated professional practice and negotiate when and how to interface with mainstream hospital services. The midwives talk of the dilemma of competing discourses about birth. Decisions to transfer to hospital in labour is fraught with concerns about the woman's and the midwife's autonomy. Hospital transfers crystallise midwives' sense of professional vulnerability. Practical implications – Maternity services organisation in Ireland commits virtually no resources to community midwifery. Home birth is almost entirely dependent upon a small number of SECMs. Although there is a "national home birth service", it is not universally and equitably available, even to those deemed eligible. Furthermore, restrictions to the professional indemnification of home birth midwives, effectively criminalises midwives who would attend certain women. Home birth, already a marginal practice, is at real risk of becoming regulated out of existence. Originality/value – This paper brings new insight into the experiences of midwives practicing at the contested boundaries of contemporary maternity services. It reveals the inappropriateness of a narrowly professional paradigm for midwifery. Disciplinary control of individuals by professions may countermand claimed "service" ideologies. <ack> <x xml:space="preserve"> Acknowledgements </x> This paper is derived from a doctoral study that was funded by an Irish Health Research Board (HRB) Clinical Fellowship in Nursing and Midwifery; Grant No. NM/2006/5. </ack>